Industrial development - "Kulkarni, M. R." (New Delhi, 1991)
The need for a new edition was felt owing to many important developments and significant changes which have taken place in the field of industrial development in India since the publication of the last edition. The growth rate of national income as well as industrial production has increased substantially putting the economy on a higher growth path. The policy of liberalisation pursued in recent years has transformed the industrial economy bringing about a greater of competitiveness and efficiency.
Keywords: Industries India